Ashes scattered in the wind: The Romanies as Marginalised Victims of Racial Persecution, Genocide and the Holocaust - Botha, Robynne (Department of Political Studies, 2020)
The experiences of the Romanies on the European continent have been marked by centuries of prejudice, abuse, slavery and murder. Central to this history of oppression is the Nazi regime’s racial persecution and genocide of the Romanies during the Holocaust. However, in the Federal Republic of Germany, the devastating experiences of the Romanies during the Holocaust received minimal attention in the decades that followed. As such, this thesis aims to answer the question: Did the transitional justice process in the Federal Republic of Germany, in the aftermath of the Third Reich, fail Romanies as victims of racial persecution, genocide and the Holocaust? It provides an overview of the suffering experienced by the Romanies at the hands of the Nazi regime, situating their plight within the framework of racial persecution, genocide and the Holocaust. It then analyses how this was addressed by the transitional justice process undertaken in the Federal Republic of Germany after the fall of the Third Reich, focusing on the mechanisms of retributive justice, as well as material and symbolic reparations. Examining how, within each of these mechanisms, Romanies were marginalised as victims, the thesis illustrates that the transitional justice process did indeed fail them. In addition, it broadens the discussion by looking at how Romaphobia is both a cause and a consequence of this marginalisation. As such, the thesis illustrates how the transitional justice process also failed Romanies by not denouncing Romaphobia, but rather inadvertently reinforcing it, thus being partly to blame for the continued presence of Romaphobia in the Federal Republic of Germany. In so doing, the thesis highlights the importance of redressing the wrongs committed against victims, emphasising the need for transitional justice mechanisms in the aftermath of violence and human rights abuses.